THE EFFECT OF SALINITY ON SOME ENDOCOMMENSALIC CLIMATES FROM SHIP WORMS - SANTAKUMARI, V (Fishery Technology, 2017)
The ciliates, Nucleocorbula adherens, Boveria teredinidi, Trichodina balakrishnia, Thingmozoon fencheli and Nyctothereus marina, live inside the mantle cavity of the shipworms in the estuaries and backwaters of the south-west coast of India. Seasonal incidence and relative abundance of these ciliates showed that they were more abundant during the low saline than the high saline periods. Eventhough these ciliates canendure higher salinities through gradual acclimatization of their habitat it was found that they prefer low salinity for active growth and healthy existence.